To compare COVID-19 disease in elderly (young old and elderly-old) in a tertiary care center - Ravi Krishnegowda; Avinash Hanbe Rajanna; Bhargav V Bhat; Yamini Marimuthu (Asian Journal of Medical Sciences, 2022)
Background: SARS‐Cov‐2 is a coronavirus that caused the coronavirus disease 2019 (COVID‐19) disease outbreak in late 2019 in Wuhan China. By early 2020, the disease had rapidly spread across the world and was declared a global pandemic as a public health emergency of international concern. The mechanisms behind the behavior of SARS-cov-2 in the elderly include immunosenescence and related impaired antiviral immunity, mature immunity, and related hyper-inflammatory responses. We aim to summarize the clinical features and outcomes of elderly COVID-19 patients and compare the difference between young-old patients (60–74 years old) and elderly-old patients (≥75 years old). Aims and Objective: (1) The aim of the study was to compare the clinical and biochemical profile of young-old patients and elderly-old COVID-19 patients. Materials and Methods: A cross-sectional study was conducted on a total of 389 patients, during the study period from March 2021 to September 2021. Case record form with follow-up chart was used to record the duration of disease, history of treatment, and complications. Patients underwent biochemical investigations. Results: The study includes 389 patients, 331 were not young-old and 58 were elderly-old. Mean age of young-old group 65.01±4.10 years and elderly-old group 80.74±5.35 years. Mortality in elderly-old group (29.3%) and young-old group (15.4%) with significant P=0.02. Comparing inflammatory markers such as total leucocyte count and neutrophil count are more in elderly-old than young-old COVID-19 patients, this difference is statistically significant P<0.005. Conclusion: Elderly patients usually have chronic comorbidities and are likely to have a severe or critically severe condition. They could show atypical symptoms. Elderly-old patients tend to have more complications than young-old patients during hospitalization. Careful nursing, observation, and systemic treatment are very important in elderly patients.